Gospel [videorecording (DVD)] - Harris, Shayla; Holman, Stacey; Gates, Henry Louis, Jr; Gates, Henry Louis, Jr; Carr, Jekalyn, 1997-; Clark-Terrell, Twinkie; Lawrence, Donald, 1958-; Warwick, Dionne; Flunder, Yvette A.; Haynes, Frederick D., 1960-; Moss, Otis, III, 1970-; Warnock, Raphael G.; et al. (PBS, 2024)
"From acclaimed scholar Henry Louis Gates, Jr., Gospel explores Black spirituality through sermon and song. From the blues to hip-hop, African Americans have been the driving force of sonic innovation for over a century. But, while musical styles come and go, there is one sound that has been a constant source of strength, courage, and wisdom. It is a message that resounds from the pulpit to the choir lofts on any given Sunday -- one of good news in bad times: gospel. Since the time of the sorrow songs, Black sacred music was a cathartic and confidential way to communicate the anger and frustration of living as a Black person in America. Even now, gospel continues to evolve and remains a source of cultural affirmation and sustenance. Over the course of four hours, Gospel explores how class, gender, cultural innovations and consumer technologies -- such as records, radio, television and the internet -- shaped the development of Black preaching and gospel over the centuries."--Container.